Dakwah Melalui Youtube: Tantangan Da’i di Era Digital - Mutrofin, Mutrofin (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2018)
This paper discusses da'wah (proselytising) through social media. The prevailing method of da'wah used by da'i currently is considered to still tend to be traditional and monotonous. As a result, the message delivered to mad'u was not well conveyed. This is certainly a challenge that must be answered so that the message can be well received by audiences. Therefore, the method of da'wah should be formulated in accordance with the demands of the times and technological developments is required nowadays. Social media is one tool that is suitable for preaching in the current era of modernization. By using YouTube propaganda material can be easily accepted among the wider community. Using Anthony Mayfield's social media theory, preaching through social media is at least able to answer the challenge